Кваліметрічніе оцінювання пакетів різнорідної інформації алгебро-логічними методами при побудові моделей розподіленного віртуального університету - Усачов, В. О. (ХНУРЕ, 2024)
The object of the study is a method for constructing a data structure and a method for processing data of heterogeneous structure for an intelligent system for evaluating complex objects, which can be used in the analysis of educational materials. The aim of this work is to develop a method of intelligent qualimetric evaluation for assessing complex objects. Tasks include modeling data structures, creating control algorithms, and developing an effective user interface. The goal is to create functionality for studying, adapting and evaluating objects using intelligent algorithms. The result is a developed intelligent system that can effectively evaluate packets of heterogeneous information.
Keywords: кваліметрічніе оцінювання; алгебро-логічні методи; віртуальний університет